Kribiodorum Kieffer (= Stelechomyia Reiss) (Diptera: Chironomidae) extends into the Oriental region: three new species and expanded diagnoses - Cranston, Peter S. (Zootaxa, 2018)
Kribiodorum Kieffer, an otherwise North American and African genus of Chironomini (Diptera: Chironomidae), extends to the Oriental region through two new species. An adult male and female of Kribiodorum malicky sp. n. is newly described from Thailand, and from Brunei (Borneo) a pharate male and the pupa of Kribiodorum belalong sp. n. is described. Additionally, from Namibia (s.w. Africa) a 'manuscript' taxon is described formally with co-authorship of the late Arthur Harrison as Kribiodorum kunene sp. n. Males of the new species and the sole new pupa conform substantially to generic diagnoses based on the North American Kribiodorum perpulchrum (Mitchell). Examination of specimens of African Kribiodorum pulchrum Kieffer and N. American K. perpulchrum confirms their morphological similarity and reaffirms the junior synonymy of Stelechomyia Reiss designated for the North American species. Kribiodorum expands the number of genera of Chironomidae with African and Asian representatives, although unusual in its absence from Australia yet presence in the Nearctic.